Fishes of the Minnesota Region - Phillips, Gary L. (Book collections on Project MUSE., 1978)
From Northern Pike to the Walleye, this is the definitive guide to all of Minnesota?s 149 kinds of fishes. Illustrated with over 80 color photographs, this book will appeal to enthusiastic anglers as well as curious naturalists. Along with a guide to ide.